A strategy for accurately and sensitively quantifying free and esterified fatty acids using liquid chromatography mass spectrometry - Feng, Xiaohui; Wang, Juan; Tang, Zhonghai; Chen, Bingyao; Hou, Xinhua; Li, Jing; Feng, Shengnan; Li, Peng; Meng, Qingshi (Frontiers in Nutrition, 2022)
Fatty acid (FA) composition of foods dictates a diversity of aspects regarding food quality, ranging from product shelf life, sensory properties to nutrition. There is a challenge to quantitate FAs using liquid chromatography-mass spectrometry due to poor ionization efficiency and matrix effects. Here, an isotopic-tagged derivatization strategy was established to accurately and sensitively quantify free and esterified FAs. After derivatization reaction, the detection sensitivity of FAs was remarkably improved and the limit of quantitation was lower than 100 ng/L. The quantitative errors caused by matrix effects were diminished benefiting from isotope-derivatized internal standards. The established quantitation strategy was successfully applied to verify both free and esterified FA contents in meat after different post-harvest procedures, finding that free polyunsaturated FAs increased significantly during freezing process.